The Analysis Of Batak Simalungunese Varieties Of Talk Between Pematang Raya And Saribu Dolok - Frans Dhaniko Saragih; Nico Sahpudan Simorangkir; Alifizhar Maulana; Rahmadsyah Rangkuti (Departement of Mathematics Education, 2024)
Language and society are intrinsically linked, with every society having a distinctive vocabulary. This study investigates the varieties of the Batak Simalungunese language, focusing on dialectal and idiolectal variations between Pematang Raya and Saribu Dolok in North Sumatra, Indonesia. Using a descriptive qualitative approach, data were collected through observations and interviews with eight native speakers aged 35-50. The research reveals significant linguistic variations between the two regions, manifesting in dialectal and idiolectal differences. Notable variations were found in vocabulary, pronunciation, and grammatical patterns. The study contributes to the broader understanding of language diversity in Indonesia and provides insights into the rich linguistic tapestry of the Batak Simalungunese community. These findings highlight the importance of studying regional language variations and their implications for cultural identity and communication within multilingual societies.